The organisation of a land occupation : a case study of Marikana, Cape Town - Teo, Rayner (Department of Sociology, 2016)
Land invasions are a nationwide concern in South Africa. Though the academic literature and the media both assert that land invasions are highly-organised activities, "organisation" can cover (or conflate) a wide range of phenomena. What is the nature of "organisation" in a land invasion and the resulting informal settlement? Drawing on mainstream social movement theory, I present and interpret evidence for how Marikana informal settlement in Cape Town took shape in August 2014. The land invasion emerged and succeeded not because of formal organisation (or indeed the tactics of an unknown collective actor - the "Third Force" hypothesis), but because of the political opportunity structure that the settlers faced, which they were only partially aware of; the networks and information that they were able to tap; and the identities and cultural frames that defined individual Marikana settlers and guided their actions. The fact that the majority of Marikana settlers were not connected to any mobilisation attempt - nor indeed knew anyone in Marikana before they arrived - shows that neither formal organisation nor informal activist networks are sufficient to explain Marikana's explosive growth. Rather, what enabled the invasion was the passive network (Bayat 1997a) of people sharing common, overlapping identities and recognising a common interest between each other, who came together in a space of opportunity. I then turn to evidence of organisational activity as the land invasion developed into an informal settlement. Marikana residents organised structures of grassroots governance at various levels, engaging externally while stratifying internally. External players and the eviction process were crucial in forging the bottom-up governance structures that emerged. While these structures almost immediately began to resemble the repertoire of organisational routines which was familiar to the residents, some of the practices they adopted were more in line with the neighbourhood's status as a new informal settlement under consolidation. However, community leaders came and went, while episodes of infighting and conflict broke out sporadically as committees lost legitimacy and faced accusations of corruption, illustrating the dynamic and uncertain nature of the new informal settlement. The trend of increasing formalisation and bureaucratisation was not a linear progression. Finally, an episode of protest followed by violent clashes with a neighbouring community marked the culmination of a tactical trajectory of attempts to engage with the state. This study develops and problematises the notion that land invasions are "organised," and - in the particular case of new informal settlements - helps to close the gap in knowledge about leadership and grassroots organising in South African social movements that others (Runciman 2011; Drivdal 2014, 20-21) have identified. And since millions of South Africans still live in inadequate housing, there is scope for agents on all sides - from policymakers to social movement participants - to reach a more systematic and productive understanding of how to deal with the inevitable formation of new informal settlements.